A Scoping Review on the Opportunities for Social Engagement and Cognitive Frailty in Older Adults - Sally Fowler Davis; Charlotte Benkowitz; Carol Holland; Alan Gow; Charlotte Clarke (Frontiers Media S.A., 2024)
Cognitive frailty (CF) is defined as the clinical syndrome of the combination of physical frailty and cognitive impairment, without dementia. Numerous risk factors for CF have been previously identified but this scoping review focusses on the critical need for social engagement and the association with cognition. The focus of this scoping review on the opportunity for social engagement rather than on perception or experience of loneliness. Based on the results of 55 studies were synthesised into four social engagement categories, namely participation, household, network, and habitat. Social engagement is associated with maintaining or improving cognition, particularly through active participation in social roles. Habitat (i.e., rural or urban settings) also influences cognition and the challenge is to enable social participation.